Use of Ayurveda in the Treatment of Type 2 Diabetes Mellitus - Allison Gordon MD Candidate; Zankhana Buch MD; Vanessa Baute MD; Remy Coeytaux MD (SAGE Publishing, 2019)
Background Ayurveda is an ancient medicine practice that is emerging in the United States as a complementary and alternative treatment for chronic illness. Type 2 diabetes is a chronic illness that has major long-term implications for individuals suffering from the disease as well as the health-care system as a whole. Modifications in diet, exercise, and lifestyle are all important factors in successful treatment of type 2 diabetes and are incorporated into the ancient Indian medicinal practice of Ayurveda. Review Summary: This review summarizes the available evidence for the use of Ayurvedic therapies in the treatment of type 2 diabetes. For the treatment of type 2 diabetes, Ayurvedic practices primarily emphasizes the use of herbal supplements; however, exercise, weight management, and various supplemental procedures are included in Ayurvedic practices. The goal of Ayurvedic practices on the treatment of type 2 diabetes like in Western medicine focuses on bringing the hemoglobin A1c (HbA1c) value into a therapeutic range. Where Ayurveda differs is that it looks at the functionality of a person in the context of striking a balance between the life forces or doshas that each individual possesses. Finally, this article includes a case study received from AyurVAID clinic in Bangalore, India that details the specific Ayurvedic intervention used in a patient, bringing his HbA1c from a level of 11.2 to 5.7 over the course of 9 months. Conclusion Patients with type 2 diabetes may inquire about current complementary and alternative therapies available for the treatment of their disease. Awareness of such modalities is necessary for effective patient counseling and care. The benefits of offering a wide array of treatment options include possible reduction of HbA1c and of comorbidities with adjunct use of supplements and mind-body practices.